Diabetes, depressive symptoms, and functional disability in African Americans: the Jackson Heart Study - Kalyani, Rita Rastogi; Ji, Nan; Carnethon, Mercedes; Bertoni, Alain G.; Selvin, Elizabeth; Gregg, Edward W.; Sims, Mario; Golden, Sherita Hill (Journal of diabetes and its complications, 2017)
To investigate the degree to which comorbid depression contributes to the relationship of diabetes with functional disability in African Americans (AAs), a population at high-risk for complications. We examined 2989 African Americans (AAs) in the Jackson Heart Study who had diabetes and depressive symptoms (CES-D) assessed at baseline. Overall functional disability was defined as the inability to perform at least one task of daily living. Multivariable logistic regression models explored the association of diabetes and depressive symptoms with functional disability. Prevalence of overall functional disability was highest with both diabetes and depressive symptoms (54%), similar with diabetes alone (31%) or depressive symptoms alone (33%), and lowest with neither (15%). Adjusting for demographics, smoking, BMI, cardiovascular comorbidities, and hsCRP, the association of depressive symptoms alone (OR=2.30,95% CI 1.75–3.03) and both diabetes and depressive symptoms (OR=2.75,1.88–4.04) with overall functional disability was significant, but not for diabetes alone (OR=1.26,0.95–1.67), compared to neither. In regression analyses including any diabetes and any depressive symptoms together in models, the main effect of depressive symptoms but not diabetes was associated with overall functional disability, and the interaction term was not significant (p-value=0.84). Functional disability was highest among AAs who have both diabetes and depressive symptoms; the latter was a stronger contributor. Future studies should explore mechanisms underlying functional disability in diabetes, particularly the role of depression.